Life History and Origin of the Camelids Provisioning a Mass Killing Sacrifice During the Chimú Period: Insight from Stable Isotopes. (2nd July 2020) - Dufour, Elise; Goepfert, Nicolas; Le Neün, Manon; Prieto, Gabriel; Verano, John W.
ABSTRACT : The site of Huanchaquito-Las Llamas, situated in the Moche Valley, Peru, dated to the Late Intermediate Period (AD 1100-1470), represents a single event mass killing of children and domestic camelids of the Chimu society. Reconstruction of the life histories of 82 camelid individuals based on stable isotope analysis of bone collagen indicates that they originated from the lowlands. Isotopic inter-individual variability indicates diversity in dietary sources, consisting of wild plants and cultigens, grown in water-limited and non-water-limited conditions, as well as a large proportion of C4 plants, suggesting that the animals originated from various herds that were differently managed. In contrast, uniformity in terms of restricted coat colour and young age could suggest that the animals derived from specialised herds. It is possible that the requirement in a short period of time for a massive number of animals meeting certain criteria exceeded the capacity of these herds. This study presents the largest isotopic dataset measured at a single pre-Hispanic site so far and the first to record herding practices for the Chimú society. Comparison with previous isotopic datasets shows differences between ritual and non-ritual groups, as well as diversity in pastoralism practises through time in the Central Andes.